Volume 3: 17th International Conference on Design Education (DEC) 2020
DOI: 10.1115/detc2020-22027
|View full text |Cite
|
Sign up to set email alerts
|

Who, What, and When? Exploring Student Focus in the Capstone Design Experience

Abstract: Product development is a key component of engineering education taught at a number of universities through their capstone design course. This course provides students with an opportunity to apply their newly obtained knowledge in engineering to design, build, and test working prototypes. This educational approach also encourages students to place additional attention on time and group management. As students walk through the design process, their focus fluctuates between group organization, product development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Dong et al (2004) review design documentation and verbal communications of student design teams to compare performance and semantic coherence (Dong, 2005). They found positive correlations between semantic similarity and team performance, agreeing with previous studies (Ball et al , 2020; Martin and Foltz, 2004). These studies however take a posteriori approach by reviewing previously completed projects and their respective documentations.…”
Section: Relating To Academic Researchsupporting
confidence: 91%
See 2 more Smart Citations
“…Dong et al (2004) review design documentation and verbal communications of student design teams to compare performance and semantic coherence (Dong, 2005). They found positive correlations between semantic similarity and team performance, agreeing with previous studies (Ball et al , 2020; Martin and Foltz, 2004). These studies however take a posteriori approach by reviewing previously completed projects and their respective documentations.…”
Section: Relating To Academic Researchsupporting
confidence: 91%
“…One of the most influential factors internal to an organization when performing NPD is the ability to build a collective understanding of the task (Bittner and Leimeister, 2014). Multiple studies have confirmed this phenomenon showing improved success of teams with a shared understanding (Ball et al , 2020; Ball and Lewis, 2018b; Koutsikouri et al , 2008; Langan-Fox et al , 2004; Mathieu et al , 2000; Mohammed et al , 2010). Building a shared understanding within heterogenous product teams requires a top down approach of aligned objectives along with a bottom up realization of integrated project components (Austin et al , 2007).…”
Section: Relating To Academic Researchmentioning
confidence: 81%
See 1 more Smart Citation
“…Because selfmanagement is so interdependent with employability skills such as teamwork and inter-communication, most students performing capstone projects did not explicitly report improvements in this area (Keller et al, 2011). However, efficient time management focused on the required course deliverables, as well as group cohesion, resulted in the most significant outcomes (Ball et al, 2020).…”
Section: Time Managing -Planning and Organizingmentioning
confidence: 99%
“…Specifically, topic modelling has been used in product design for studying the impact of various interventions on design (Fu, Cagan & Kotovsky 2010; Gyory, Kotovsky & Cagan 2021 a ), to comparing human and AI teams (Gyory et al 2021 b ), to analysing capstone team performance (Ball, Bessette & Lewis 2020), to visualising engineering student identity (Park et al 2020), to deriving new product design features from online reviews (Song et al 2020; Zhou et al 2020) and identifying areas for cross-domain inspiration (Ahmed & Fuge 2018). By plotting a design team’s topic mixtures before and after a manager intervention, Gyory et al (2021 a ) were able to measure the result of the design intervention and whether it helped to bring the team back on track.…”
Section: Introductionmentioning
confidence: 99%